Thermoeconomic Analysis of Batch Type Grain Dryer Machines in District X Region - Okto Barita; Dahlan Buhungo (CV. HEI PUBLISHING INDONESIA, 2025)
Drying grain is a crucial stage in the post-harvest process to maintain product quality and storability. The objective of this study is to evaluate the technical and economic performance of a batch-type grain dryer that uses heat from the indirect combustion of rice husks via a hot-air circulation system. The research was conducted in District X, X Regency, using a machine with a capacity of approximately 6 tons per cycle and an average drying duration of 8 hours. The observed parameters included drying-chamber temperature, moisture content, relative humidity, thermal efficiency, specific power requirement, drying yield, drying rate, fuel consumption, and overall energy efficiency. The results indicated that the drying-chamber temperature ranged from 28 to 32°C, while the grain moisture content decreased from 23–25% to 15.4%. The highest thermal efficiency reached 85.57%, with an average specific power requirement of 0.00188 kWh/kg and a drying yield of 97.68%. Using 120 kg of rice husk fuel per cycle produced a drying efficiency of 15%. The drying cost was IDR 53.55/kg, and the break-even point was reached after 1,740 hours of operation per year. These findings demonstrate that batch-type grain dryers are technically reliable and economically feasible for grain drying at the farm level.